2005
DOI: 10.1212/01.wnl.0000150544.00016.69
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular abnormalities in a population of children with neurofibromatosis type 1

Abstract: Neurofibromatosis type 1 (NF1) is associated with vasculopathy, which may result in a variety of cerebrovascular complications. The purpose of this study was to evaluate the spectrum of cerebrovascular disease in a pediatric population with NF1. Of 316 patients with NF1 who underwent brain MRI, 8 (2.5%) children were reported to have an abnormality of the cerebrovascular system, including narrowed or ectatic vessels, vascular stenoses, aneurysm, and moyamoya.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
173
3
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(189 citation statements)
references
References 8 publications
12
173
3
1
Order By: Relevance
“…The majority of recent studies examining Nf1 haploinsufficiency have focused on the role of NF1 in modulating the tumor microenvironment of plexiform neurofibromas and optic gliomas (4 -6,31 -36). However, both clinical data from NF1 patients and experimental studies in Nf1þ/2 mice support the hypothesis that haploinsufficiency of NF1 (Nf1) results in a range of non-malignant phenotypes, including cerebrovascular disease (40), renal vascular hypertension (41 -43) and osseous abnormalities (10,13 -15,17,44), suggesting that haploinsufficient NF1 contributes to pathogenesis in multiple lineages. Our present study sought to understand the role of haploinsufficiency of NF1 (Nf1) in disrupting normal MSPC differentiation.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The majority of recent studies examining Nf1 haploinsufficiency have focused on the role of NF1 in modulating the tumor microenvironment of plexiform neurofibromas and optic gliomas (4 -6,31 -36). However, both clinical data from NF1 patients and experimental studies in Nf1þ/2 mice support the hypothesis that haploinsufficiency of NF1 (Nf1) results in a range of non-malignant phenotypes, including cerebrovascular disease (40), renal vascular hypertension (41 -43) and osseous abnormalities (10,13 -15,17,44), suggesting that haploinsufficient NF1 contributes to pathogenesis in multiple lineages. Our present study sought to understand the role of haploinsufficiency of NF1 (Nf1) in disrupting normal MSPC differentiation.…”
Section: Discussionmentioning
confidence: 83%
“…Although CFU-C cells were elevated in the Nmp4-KO mice, this only approached significance, and there was no difference in the levels of CFU-M cells between the genotypes. The precise lineage of the osteoclast and its relationship to other hematopoietic cells is controversial; however, there are a number of studies supporting the hypothesis that the osteoclast lineage branches to terminal differentiation via the CFU-GM cells before further passage toward the monocyte/macrophage lineage [39,40]. No differences between WT and Nmp4-KO mice in CD8 + T cells were detected in the PBL (average -SD, number of mice/ experimental group 11-14; statistical differences were determined using a 2-way ANOVA).…”
Section: Nmp4 and Pthmentioning
confidence: 99%
“…In term of NF-1, eight (2.5%) patients among 316 NF-1 patients were found to have an abnormality of the cerebrovascular system [17]. Seven patients had a vasculopathy diagnosed as an incidental findings on neuroimaging, but a patient presented with ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…2 Recent studies have also demonstrated the presence of neurofibromin on the walls of vascular endothelial cells and in vascular smooth muscle cells. 3 Moyamoya disease (MMD) is a rare inherited cerebral disorder of unknown etiology characterized by obliteration of the internal carotid artery and its branches, with the concomitant development of an abnormal network of collateral vessels. Moyamoya syndrome (MMS), an acquired form of MMD, also displays the angiographic pattern of MMD, although it is usually associated with different risk factors such as NF-1, Down syndrome and previous cranial irradiation, among others.…”
Section: Introductionmentioning
confidence: 99%